(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Currently, the need to master computer technologies at the present stage of society’s development is not in doubt, however, the problem of preventing the harmful effects of the hobby of virtual technologies requires increased attention. Humanity is immersed in computers and computer networks, every day more and more people (especially children and teenagers) become addicted to computers.